Exploiting Codon-Triplets Association for Genome Primary Structure Analysis - Lousado, José (2008)
Abstract— The way evolution shapes the arrangement of synonymous codons within open reading frames (ORF) for fine tuning mRNA decoding efficiency is not yet understood. Since the ribosome has 3 tRNA binding sites, the context of triplets should be relevant to decoding fidelity and efficiency. We have developed a software application for large-scale analysis of codon-triplet associations to shed new light into this problem. The developed algorithms identify codon-triplets context biases, allowing for large scale comparative codon-triplet analysis and for identification of alterations to the standard genetic code.